2013
DOI: 10.1063/1.4815945
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity from approach-to-equilibrium molecular dynamics

Abstract: We use molecular dynamics simulations to study the thermal transport properties of a range of poor to good thermal conductors by a method in which two portions are delimited and heated at two different temperatures before the approach-to-equilibrium in the whole structure is monitored. The numerical results are compared to the corresponding solution of the heat equation. Based on this comparison, the observed exponential decay of the temperature difference is interpreted and used to extract the thermal conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
103
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(107 citation statements)
references
References 22 publications
3
103
0
1
Order By: Relevance
“…This expression is fitted to the temperature gradient obtained from the simulations to determine κ. More details on the methodology can be found elsewhere [10,25,36]. …”
Section: A Aemd Simulationsmentioning
confidence: 99%
“…This expression is fitted to the temperature gradient obtained from the simulations to determine κ. More details on the methodology can be found elsewhere [10,25,36]. …”
Section: A Aemd Simulationsmentioning
confidence: 99%
“…[9,21,22] For the simulations of the present study, using the two fitting procedures gives results as shown in Fig. 8.…”
Section: Extrapolating the Bulk Thermal Conductivitymentioning
confidence: 99%
“…In a different, time-dependent approach, temperature transients can also be used to study the thermal response. [6,7] Recently, [8,9] we have shown that when a simulated temperature pulse establishes a step-difference temperature profile in a material, the transient to the equilibrium temperature is exponential, making it easy to extract a typical decay time of the thermal pulse. Using the heat equation, the thermal conductivity can be obtained from this decay time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work we offer some insight on this problem by performing unbiased (i.e., with no a priori guess) AEMD simulations [25,26] on pristine graphene monolayers with L z up to a size of 0.1 mm. Our goal is to ultimately state whether the claimed κ ∼ log L z divergence is indeed observed by a direct numerical estimate and, if so, whether this behavior drives to a divergent thermal conductivity for arbitrarily long samples.…”
mentioning
confidence: 99%